Impact of Vedic Mathematics on Students' Performance - Yasir, Yasir; Hussain, Amil; Khan, Hasnain; Kania, Nia (EDUPEDIA Publisher, 2026)
Purpose – Mathematics is a foundational subject essential to daily life and professional practice; however, many students perceive it as difficult and uninteresting due to rigid rules and complex procedures, which often lead to a fear of mathematics. This study aims to examine the effectiveness of Vedic Mathematics (VM) training in improving students’ mathematical performance and attitudes toward mathematics. Methodology – An experimental research design was employed involving 146 undergraduate students from business management and commerce programs. Participants were divided into an experimental group and a control group using a non-random sampling technique. The experimental group received one week of Vedic Mathematics training focused on mental calculation strategies, while the control group followed conventional instructional methods. Data were collected using timed pre-test and post-test assessments to measure mathematical performance, along with a self-developed questionnaire to assess mathematics phobia and interest. Data analysis was conducted by comparing pre- and post-test results between groups. Findings – Students who received Vedic Mathematics training demonstrated improved calculation speed and accuracy, increased interest in mathematics, and reduced mathematics phobia compared to the control group. These results indicate that VM training positively influences both cognitive performance and affective attitudes toward mathematics. Novelty – This study contributes empirical evidence on the effectiveness of Vedic Mathematics as an alternative instructional approach in higher education, particularly in addressing affective barriers in mathematics learning. Significance – The findings are beneficial for educators, curriculum developers, and higher education institutions seeking instructional strategies to enhance students’ mathematical proficiency, confidence, and engagement.